Multitrait analysis of fresh-cut cantaloupe melon enables discrimination between storage times and temperatures and identifies potential markers for quality assessments. (15th February 2018) - Amaro, Ana L.; Spadafora, Natasha D.; Pereira, Maria J.; Dhorajiwala, Rakhee; Herbert, Robert J.; Müller, Carsten T.; Rogers, Hilary J.; Pintado, Manuela
Highlights: Volatile Organic Compounds changed with over time and with storage temperature. Low temperature (0 °C) preserves Vitamin C and reduces microbial load. Higher temperature (10 °C) maintains esters balance and phenolic content. VOC markers correlate with vitamin C loss for storage time and temperature. Abstract: Fresh-cut cantaloupe melon is valued for its aroma but is highly perishable. Temperature of storage (typically 0–5 °C) is critical for maintaining fresh-cut melon quality, but often reaches 10 °C during transportation and in retail outlets. A comparison amongst 0, 5 and 10 °C storage temperatures for fresh-cut melon over 14 days reveals that storage at 0 °C is optimal for avoiding increases in microbial load and loss of vitamin C especially at later time points. However, higher temperatures maintain better the balance of esters (acetate versus non-acetate) and phenolic content. The whole volatile organic compound (VOC) profile can be used to discriminate both time and temperature effects especially at earlier time points. Potential VOC markers for changes in vitamin C from day 0 to day 6 of storage (3-methyl butane nitrile) and temperature (limonene) are identified through a multi-trait analysis.